Advanced Calculus - Folland, Gerald B. (New Jersey : Prentice Hall, 2002)
Designed for undergraduate courses in advanced calculus and real analysis. This text presents a unified view of calculus in which theory and practice reinforce each other. It covers the theory and applications of derivatives (mostly partial), integrals, (mostly multiple or improper), and more
Includes bibliography and index.
Keywords: Calculus